EFFECTIVENESS OF ICE MASSAGE ON LI4 ACUPRESSURE MERIDIAN POINT IN LABOUR PAIN PERCEPTION AMONG THE PARTURIENT MOTHERS - DR.PROF.K.LATHA (International Journal of Pharma and Bio Sciences, 2016)
Over the years, labour pain management studies have focused on the use of drugs that affect sensory awareness of pain, which may have the additional effect of impeding women’s active participation in giving birth. So any technique that provides safe and effective pain reduction without serious side effects can be given by any health professionals is a definite advance. To assess the effect of ice massage on LI4 acupressure meridian point in labour pain perception, a quantitative approach, randomized time series clinical trial on 180 parturient mothers by simple random sampling was conducted. Multiple institution of ice massage over the LI 4 (Large intestine 4) acupressure meridian point on the left hand of the parturient mothers was given. Subjects were assessed for pre and post test labour pain perception using Visual analogue scale. Results showed a high statistical significant difference in the perception of labour pain at p< 0.001 level (t=19.93, p=0.001***). Study concluded that ice massage over the LI4 acupressure meridian point was effective in the reduction of the labour pain perception, and hence it can be a safe and effective tool to reduce the intensity and the unpleasantness of pain from early labour contractions.